2021
DOI: 10.3390/nano11071703
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Lithium and Sodium Storage Properties of TiO2(B) Nanobelts by Doping with Nickel and Zinc

Abstract: Nickel- and zinc-doped TiO2(B) nanobelts were synthesized using a hydrothermal technique. It was found that the incorporation of 5 at.% Ni into bronze TiO2 expanded the unit cell by 4%. Furthermore, Ni dopant induced the 3d energy levels within TiO2(B) band structure and oxygen defects, narrowing the band gap from 3.28 eV (undoped) to 2.70 eV. Oppositely, Zn entered restrictedly into TiO2(B), but nonetheless, improves its electronic properties (Eg is narrowed to 3.21 eV). The conductivity of nickel- (2.24 × 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Among the existing EES devices, there is a complementary relationship between metal-ion batteries (MIBs) and supercapacitors (SCs) since the former has a high energy density, but the latter can deliver extreme power density [1][2][3][4][5]. It is recognized that increasing the power energy of the MIBs to as high as that of the SCs is intrinsically challenging, owing to the insertion/extraction of the metal ions from the corresponding electrode materials being principally essential, that is, the energy storage mechanism [6][7][8][9][10]. On the contrary, it has been demonstrated that several electrode materials that followed a redox reaction can provide more capacitances as compared with the traditionally used carbonaceous materials [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Among the existing EES devices, there is a complementary relationship between metal-ion batteries (MIBs) and supercapacitors (SCs) since the former has a high energy density, but the latter can deliver extreme power density [1][2][3][4][5]. It is recognized that increasing the power energy of the MIBs to as high as that of the SCs is intrinsically challenging, owing to the insertion/extraction of the metal ions from the corresponding electrode materials being principally essential, that is, the energy storage mechanism [6][7][8][9][10]. On the contrary, it has been demonstrated that several electrode materials that followed a redox reaction can provide more capacitances as compared with the traditionally used carbonaceous materials [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical storage of bronze–TiO 2 (TiO 2 (B)) has been recently found to be improved by doping with Ni and Zn. [ 329 ] Their findings revealed that doping with 5 at% Ni (Ni/Ti ratio of 0.02/0.05/0.08) into TiO 2 (B) successfully dilates the unit cell by 4% and creates defects that reduce the energy bandgap from 3.28 to 2.70 eV. By contrast, Zn doping is highly restricted (Zn/Ti ratio 0.02/0.05); nevertheless, it significantly improves conductivity (3.29 × 10 −9 S cm −1 ), compared to that of the bare TiO 2 (B) (1.05 × 10 −10 S cm −1 ).…”
Section: Anodesmentioning
confidence: 99%
“…Recently, TiO 2 (B) nanobelts were also reported to act as highperformance anode materials for LIBs. [188][189][190][191] Different strategies were applied to enhance the electrochemical performance of TiO 2 (B) nanobelt anodes, including compositing with other materials, [189] doping, [190] and surface engineering. [191] It has been demonstrated that anatase TiO 2 with exposed {001} facets could deliver better lithium storage performance than normal anatase TiO 2 .…”
Section: (18 Of 30)mentioning
confidence: 99%